The Influence of Website Quality and Security Privacy toward E-Loyalty with E-Satisfaction and E-Trust as Mediating Variables (Case Study on Tokopedia in Pontianak) - Yolanda, Winda B1024141024 (Jurnal Manajemen Update, 2018)
This study aims to determine the influence of website quality and security privacy toward e-loyalty of Tokopedia in Pontianak with e-satisfaction and e-trust as mediating roles. This research is a survey research conducted to understand the causal relationships between variables which are website quality, security privacy, e-satisfaction, e-trust, and e-loyalty. The questionnaire is distributed to 100 sample who are above 18 years old and have made purchase in Tokopedia. The data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method and SmartPLS 3.2.7 software used to complete the quantitative data. The result of this research shows that H1, H2, H3, H4, H6, and H7 are accepted but H5 is rejected.Keywords: website quality, security privacy, electronic satisfaction, electronic trust, electronic loyalty.Â REFERENCESÂ Ahmad, A., Rahman, O., Khan, M.N. (2017). Exploring the role of website quality and hedonism in the formation of e-satisfaction and e-loyalty: Evidence from internet users in India. Journal of Research in Interactive Marketing, Vol. 11 No. 3, pp.246-267.Â Â Â Â Â Â Â Â Â Anderson, R.E. & Srinivasan, S.S. (2003). Eâ€satisfaction and eâ€loyalty: a contingency framework, Psychology & Marketing, Vol. 20 No. 2, pp. 123-138.Â Asosiasi Penyelenggara Jasa Internet Indonesia (APJII). 2017. Pertumbuhan Pengguna Internet di Indonesia. Retrieved from https://www.apjii.or.id/Â Augusty, Ferdinand. (2006). Metode Penelitian Manajemen: Pedoman Penelitian untuk Penulisan Skripsi, Tesis dan disertasi Ilmu Manajemen. Semarang: Badan Penerbit Universitas Diponegoro.Â Augusty, Ferdinand. (2002). Structural Equation Modelling dalam PenelitianManajemen. Semarang:FE UNDIP.Â Bagozzi, R.P. & Yi, Y. (1988). On the evaluation of structural equation models. Journal of the Academy of Marketing Science, Vol. 16 No. 1, pp. 74-94.Â Boone, H. N., & Boone, D. A. (2012).Â Analyzing likert data. Journal of extension, 50(2), 1-5.Â Buttner, O.B. & Goritz, A.S. (2008). Perceived Trustworthiness of OnlineShops. Journal of Consumer Behaviour.Â Chang, K., Kuo, N., Hsu, C., & Cheng, Y. (2014). The Impact of Website Quality and Perceived Trust on Customer Purchase Intention in the Hotel Sector: Website Brand and Perceived Value as Moderators. International Journal of Innovation, Management and Technology, Vol. 5, No. 4.Â Choi, Y. & Mai, D.Q. (2018). The Sustainable Role of the E-Trust in the B2C E-Commerce of Vietnam. Global E-Governance Program.Â Chou, S., Chen, CW., Jiun, YL. (2015). Female online shoppers: Examining the mediating roles of e-satisfaction and e-trust on e-loyalty development. Internet Research, Vol. 25 No. 4, pp.542-561.Â Connolly, R. & Frank, B. (2007). Â Consumer trust in electronic commerce: social & technical antecedents. World Academy of Science, Engineering and Technology, Vol. 2 No. 4, pp. 239-248.Â Cyr, D. (2008). Modeling web site design across cultures: relationships to trust, satisfaction, and e-loyalty. Journal of Management Information Systems, Vol. 24 No. 4, pp. 47-72.Â Digital News Asia. (2017). E-Commerce review for Indonesia.Â  Retrieved from https://www.digitalnewsasia.com/digital-economy/2017-e-commerce-review-indonesiaÂ Eid, MI. (2011). Determinants of E-commerce Customer Satisfaction, Trust, and Loyalty in Saudi Arabia. Journal of Electronic Commerce Research. 12 (1). 78-93. Â FlaviÃ¡n, C., GuinalÃu, M. (2006). Consumer trust, perceived security and privacy policy: Three basic elements of loyalty to a web site. Industrial Management & Data Systems, Vol. 106 No. 5, pp.601-620.Â Ghozali, Imam. (2008). Model Persamaan Struktural, Konsep, dan Aplikasidengan Program AMOS 16.0. Semarang: Badan Penerbit Universitas Diponegoro.Â Gregg, D.G. & Walczak, S. (2010). The Relationship between WebsiteQuality, Trust, and Price Premiums at Online Auctions. Journal ofElectronic Commerce Research.Â Hansen, E. & Jonsson, E. (2013). E-loyalty in fashion e-commerceâ€“ an investigation in how to create e-loyalty.Â Kim, J., Jin, B. and Swinney, J.L. (2009), â€œThe role of etail quality, e-satisfaction and e-trust in online loyalty development processâ€, Journal of Retailing and Consumer Services, Vol. 16 No. 4, pp. 239-247.Â KivijÃ¤rvi, M., Laukkanen, T. and Cruz, P. (2007), â€œConsumer trust in electronic service consumption: a cross-cultural comparison between Finland and Portugalâ€, Journal of Euromarketing, Vol. 16 No. 3, pp. 51-65.Â Kotler, P & Keller, K. L. (2012). Principles of Marketing. 15thÂ  Edition. Pearson Education Limited: England.Â Kotler, P & Keller, K. L. (2013). Marketing Management. 14thÂ  Edition .Pearson Education Limited. England.Â Laundon, C.K. & Laudon, P. J. (2014). Management Information System 13thÂ  Edition. England: Pearson Educatin Limited.Â Â Leninkumar, V. (2017). The Relationship between Customer Satisfaction and Customer Trust on Customer Loyalty. International Journal of Academic Research in Business and Social Sciences 2017, Vol. 7, No. 4 ISSN: 2222-6990 450.Â Liu, C., Marchewka, J.T., Lu, J. and Yu, C.S. (2005), â€œBeyond concern: a privacy-trust-behavioral intention model of electronic commerceâ€, Information & Management, Vol. 42 No. 1, pp. 127-142.Â Loiacono, E.T., Watson, R.T. & Goodhue, D.L. (2002). WEBQUAL: Measure of website quality. Marketing Educators Conference: Marketing Theory and Applications, Vol. 13, pp. 432-437.Â Malhotra, Naresh K. (2010). Marketing research: an applied orientation. 6th ed., Global edition. Boston: Pearson, 929 s. ISBN 9780136094234.Â McKnight, D.H., Choudhury, V. & Kacmar, C. (2002). The impact of initial consumer trust on intentions to transact with a web site: A trust building model. The Journal of Strategic Information Systems, vol. 11, no. 3, pp. 297-323,Â McLeod, R. & Schell, G. (2004). Management Information System. 10th Edition. Pearson/Prentice Hall, 2007. The University of Virginia.Â Mekovec, R. & Hutinski, Z. (2012). The role of perceived privacy and perceivedsecurity in online market. University of Zagreb, Faculty of organization and informatics, VaraÅ¾din, Croatia.Â Â Â Morgan, R.M., and Hunt, S.D. (1994). The commitment-trust theory of relationship marketing. Journal of Marketing, 58(3), 20-38.Â Napitupulu, D. (2017). Analysis of Factors Affecting the Website Quality Based on Webqual Approach (Study Case: XYZ University). International Journal on Advanced Science Engineering Technology, Vol. 7 No. 3, ISSN: 2088-5334.Â Nikhashemi, S.R., Paim, L., Yasmin, F. & Yousefi. A. (2013). Critical Factors in Determining Customer Satisfaction Toward Internet Shopping in Malaysia. International Journal of Business and Management Invention ISSN (Online): 2319 â€“ 8028, ISSN (Print): 2319 â€“ 801X Volume 2 Issue 1 PP.44-51Â Parasuraman, V.A., Zeithaml, and Malhotra, A. (2005). E-S-QUAL: A multiple-item scale for assessing electronic service quality. Journal of Service Research, Vol. 7, No. 3, pp. 213-234.Â Patrick, A.S. (2002). Building trustworthy software agents. IEEE Internet Computing, 6(6), 46-53.Â Ranaweraa, C. & Prabhu, J. (2003). On the relative importance of customer satisfaction and trust as determinants of customer retention and positive word of mouth. Journal of Marketing Research.Â Rotter, J.B. (1967). A new scale for the measurement of interpersonal trust. Journal of Personality, 35(4), 651-665.Sadeh, Ehsan. et al. (2012). The Effect of Website Quality Dimensions on Customer Satisfaction in E-Retailing System. Middle-East Journal of Scientific Research.Â Â Â Â Â Â Â Â Â  Â Sekaran, U. & Bougie, R. (2010). Research Methods for Business: A Skill Building Approach (5th Edition). New York: John Wiley and Sons Limited.Â Singarimbun, Masri. (1999). Metode dan Proses Penelitian dalam Metode Penelitian Survei. Yogyakarta: LP3ES.Â Smith, Scott M. - Albaum, Gerald S. (2005). Â Fundamentals of marketing research. Thousand Oaks: Sage. xii, 881 s. ISBN 0-7619-8852-1.Â Statista. (2018). Indonesian e-commerce market revenue (in million U.S. dollars). Retrieved fromÂ https://www.statista.com/outlook/243/120/ecommerce/indonesia#Â Supranto, J. 2003. Metode Riset Aplikasi Dalam Pemasaran. Edisi Revisi Ketujuh.Yogyakarta: Rineka Cipta.Â Tokopedia. (2018). About Tokopedia. Retrieved fromhttps://www.tokopedia.com/Â W&S Group Research. (2015). Consumer Switching Interest on E-commerce. Retrieved from https://www.slideshare.net/WS-Group-Market-Research/marketplace-site-begin-to-dominate-ecommerce-marke-tin-indonesia-2015Â W&S Group Research. (2015). Switching In/Out E-commerce Site. Retrieved from https://www.slideshare.net/WS-Group-Market-Research/marketplace-site-begin-to-dominate-ecommerce-marke-tin-indonesia-2015Â YouGov. (2017). Top Index Rankings: Indonesia e-Commerce and m-Commerce. Retrieved fromhttp://www.brandindex.com/ranking/indonesia/2017-index/category/e-commerce-and-m-commerceÂ